Вплив металу на поверхневі характеристики напівпровідника - Il'chenko, L. G.; Il'chenko, V. V.; Lobanov, V. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2011)
Within the framework of dielectric formalism in absence of direct semiconductor-metal contact and external tension, the interaction potential has been calculated in the system with asymmetric bulk and surface characteristics of semiconductor-vacuum-metal (SVM) system taking into account distinctions in bulk properties of all three media, the charge status of semiconductor and metal surfaces as well as their microscopic structures. The continuity of image forces and respectively that of total potential as well as an unique (vacuum) level of energy scale in the SVM system are provided by correct counting spatial dispersion in the permittivity functions for both semiconductor and metal. When the thickness of vacuum gap is decreased to L < 1 nm, the contribution of structural potential to total one considerably increases because the mutual effect rises of the microscopic (atomic) structures of both two surfaces. The structural potential (which is a superposition of the microscopic structure contributions of both surfaces) has been shown to be asymmetrical and to cause a local change in the height of potential barrier within the vacuum gap as well as a lateral (at the interfaces) change in the total potential throughout the entire SVM system. The presence of metal at the distances less than the surface charge area of semiconductor changes the value of surface bending of semiconductor bands and due to further diminishing vacuum gap to distance L < 1 nm, microscopic structure of metal surface is capable to stimulate a lateral redistribution of charge density (surface states) not only at semiconductor surface but also within its subsurface region.